Effect of idalopirdine as adjunct to cholinesterase inhibitors on change in cognition in patients with alzheimer disease: three randomized clinical trials - Atri, Alireza; Frölich, Lutz (The journal of the American Medical Association, 2018)
Importance New therapeutic approaches for Alzheimer disease (AD) are needed. Objective To assess whether idalopirdine, a selective 5-hydroxytryptamine-6 receptor antagonist, is effective for symptomatic treatment of mild to moderate AD. Design, Setting, and Participants Three randomized clinical trials that included 2525 patients aged 50 years or older with mild to moderate AD (study 1: n = 933 patients at 119 sites; study 2: n = 858 at 158 sites; and study 3: n = 734 at 126 sites). The 24-week studies were conducted from October 2013 to January 2017; final follow-up on January 12, 2017. Interventions Idalopirdine (10, 30, or 60 mg/d) or placebo added to cholinesterase inhibitor treatment (donepezil in studies 1 and 2; donepezil, rivastigmine, or galantamine in study 3). Main Outcomes and Measures Primary end point in all 3 studies: change in cognition total score (range, 0-70; a lower score indicates less impairment) from baseline to 24 weeks measured by the 11-item cognitive subscale of the Alzheimer’s Disease Assessment Scale (ADAS-Cog); key secondary end points: Alzheimer’s Disease Cooperative Study-Clinical Global Impression of Change Scale and 23-item Activities of Daily Living Inventory scores. Dose group efficacy required a significant benefit over placebo for the primary end point and 1 or more key secondary end points. Safety data and adverse event profiles were recorded. Results Among 2525 patients randomized in the 3 trials (mean age, 74 years; mean baseline ADAS-Cog total score, 26; between 62% and 65% of participants were women), 2254 (89%) completed the studies. In study 1, the mean change in ADAS-Cog total score between baseline and 24 weeks was 0.37 for the 60-mg dose of idalopirdine group, 0.61 for the 30-mg dose group, and 0.41 for the placebo group (adjusted mean difference vs placebo, 0.05 [95% CI, -0.88 to 0.98] for the 60-mg dose group and 0.33 [95% CI, -0.59 to 1.26] for the 30-mg dose group). In study 2, the mean change in ADAS-Cog total score between baseline and 24 weeks was 1.01 for the 30-mg dose of idalopirdine group, 0.53 for the 10-mg dose group, and 0.56 for the placebo group (adjusted mean difference vs placebo, 0.63 [95% CI, -0.38 to 1.65] for the 30-mg dose group; given the gated testing strategy and the null findings at the 30-mg dose, statistical comparison of the 10-mg dose was not performed). In study 3, the mean change in ADAS-Cog total score between baseline and 24 weeks was 0.38 for the 60-mg dose of idalopirdine group and 0.82 for the placebo group (adjusted mean difference vs placebo, -0.55 [95% CI, -1.45 to 0.36]). Treatment-emergent adverse events occurred in between 55.4% and 69.7% of participants in the idalopirdine groups vs between 56.7% and 61.4% of participants in the placebo groups. Conclusions and Relevance In patients with mild to moderate AD, the use of idalopirdine compared with placebo did not improve cognition over 24 weeks of treatment. These findings do not support the use of idalopirdine for the treatment of AD.
Gesehen am 28.08.2019